Mewujudkan Sekolah Ramah Anak: Implementasi Disiplin Positif dalam Kurikulum Merdeka - Putikadyanto, Agus Purnomo Ahmad; Amin, Moh. Badruddin; Wachidah, Liana Rochmatul (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This article discusses the implementation of positive discipline as an approach to creating child-friendly schools in the context of the Merdeka Curriculum. The research aims to identify effective strategies for implementing positive discipline to enhance a supportive learning environment for the holistic development of children in schools, as well as its successes and challenges. The research method used is qualitative study with a descriptive analytical approach. Data were collected through participatory observation, interviews with teachers and principals, as well as analysis of school policy documents and curriculum. The results show that the implementation of positive discipline in the Merdeka Curriculum can help create an inclusive, collaborative, and supportive school culture that promotes the social-emotional development of children despite challenges in its implementation. This article provides insights into the importance of positive discipline approaches in creating child-friendly schools and offers recommendations for the development of more supportive practices and policies at the school level.